Natural hematite properties of Lampakuk, Aceh Besar iron ore extracted by precipitation method. Issue 1 (February 2021) - Rahwanto, A; Muhammad; Machmud, M N; Jalil, Z
Abstract: In this paper, the mineral content and its magnetic properties of iron ore from Lampakuk iron ore area, Aceh province were studied. The iron ore was prepared by co-precipitation method. As the results, the main mineral and chemical compositions of samples which were investigated by XRD and XRF analysis tests, showed that the Lampakuk iron ore contain Fe2O3 (86.8188%) and some minor impurities, such as SiO2, MnO, and Al2O3 in varying proportions. Compare to XRD results, it was consistent with XRF, the phase compositions of iron ore are mainly hematite (Fe2O3). The XRD revealed that hematite is the major mineral components in the Lampakuk iron ores. The magnetic properties of the samples after milling showed there has been increased in the remanent (Br) and coercivity (Hc), while the magnetic saturation (Ms) was decreased. The electron microscope identification inform that the particle were agglomerated.